2014
DOI: 10.3171/2014.1.jns131869
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of outcome in civilian gunshot wounds to the head

Abstract: A frequent problem in estimating logistic regression models is a failure of the likelihood maximization algorithm to converge. In most cases, this failure is a consequence of data patterns known as complete or quasi-complete separation. For these patterns, the maximum likelihood estimates simply do not exist. In this paper, I examine how and why complete or quasi-complete separation occur, and the effects they produce in output from SAS ® procedures.I then describe and evaluate several possible solutions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(125 citation statements)
references
References 67 publications
10
115
0
Order By: Relevance
“…[3,16] Previous studies have reported that the patients admitted for FAI were usually 20-35 years old and predominantly male. [4,8,10,16,18] In agreement with the literature, our study found that predominantly young males were the victims of FAIs.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…[3,16] Previous studies have reported that the patients admitted for FAI were usually 20-35 years old and predominantly male. [4,8,10,16,18] In agreement with the literature, our study found that predominantly young males were the victims of FAIs.…”
Section: Discussionsupporting
confidence: 92%
“…[35] Former studies have reported that GCS was inversely proportional to mortality. [4,10,12,16,18,30,3335,36] Complying with the literature data, an inverse relationship between GCS and mortality was also detected.…”
Section: Discussion Concerning Emergency Procedures Applied For Faissupporting
confidence: 60%
See 2 more Smart Citations
“…Penetrating brain injury from a high-velocity projectile creates a complex pattern of permanent tissue damage. The bullet track left in the wake of the missile creates a potential nidus for foreign body migration, local brain necrosis, and external contamination of devitalized wound tissues (15).…”
Section: Discussionmentioning
confidence: 99%